Transformation of Physics Learning through Digital Media at Universitas Samudra - Teuku Hasan Basri; Ilyas Ilyas; Nuraini Nuraini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
The transformation of learning in the digital era encourages universities to utilise technology in improving the quality of the learning process. This study aims to analyse the transformation of physics learning through the use of digital media in the Digital Learning Innovation course at Samudra University. This study uses a qualitative descriptive approach supported by simple quantitative data. The subjects of the study were 14 2nd-semester students who took courses with a weight of 2 credits. Data collection techniques are carried out through observation, questionnaires, and documentation. The results of the study show that the implementation of digital media such as interactive presentations, learning videos, online learning platforms, and media design applications is able to create a more interactive and varied learning process. The level of student participation in learning is relatively high, with the majority of students in the active and very active categories. The results of the questionnaire showed that students' perception of the use of digital media was in the very good category, with an average score of 4.24. In addition, students can produce digital learning media products with an average score of 85, which is included in the very good category. Thus, the use of digital media has been proven to be able to increase student involvement, motivation, and creativity in physics learning.